Dampak Ekonomi Makro Terhadap Yield Surat Berharga Negara: Studi Empiris Di Indonesia - Muhammad Ichsan; Lestari Agusalim; Zed Abdullah (Trunojoyo University of Madura, 2018)
The increasing integration of the world economy and the large share of foreign ownership of the Government Securities (SBN), then changes in economic policies in developed countries affect the pressure on financial markets in emerging market countries. This study analyzes the effect of macroeconomic factors on 10-year tenor Government's yields issued by the Government of Indonesia for the period 2012-2017. Using the Vector Error Correction Model (VECM) results in long-term USD/IDR, Oil Price, Credit Default Swap (CDS) are negatively significant, while Brazilian State Bonds (ON Brazil) have a significant positive effect on SBN yield. Based on the analysis of Impulse Response Function (IRF), the shock of yield on ON Brazil, CDS, JIBOR, USD / IDR and US Treasury (UST) responded positively by the yield SBN in each period, but the shock by Oil Price responded negatively by the yield of SBN. The result of Forecast Error Variance Decomposition (FEVD) analysis shows that UST variable is the biggest variable contribution influence to Indonesia SBN yield, followed by CDS and ON Brazil.